Addidit antiquo virtus nova lumina coelo: astronomijos observatorijos kūrimas ir veikla Vilniaus Stepono Batoro universitete 1919–1939 metais - Agnė Poškienė; Julija Jonušaitė (Lietuvos Istorijos Studijos)
This article examines the establishment and operation of the astronomical observatory of Vilnius Stefan Batory University in 1919–1939. The interwar history of the observatory has been mainly discussed and analyzed in the works of physicists and astronomers, but the topic has not received more in-depth attention from historians. Extensive archival material is used to study the location and space chosen for the observatory complex, the development of its construction works, the scientific research carried out, the observatory’s library, and the periodical scientific publication “The Bulletin of Vilnius Astronomical Observatory”. The article draws attention to the period of the observatory’s last years of operation and its handover to Kaunas astronomers, which is not reflected in historiography.